2020
DOI: 10.1590/0103-6440202003622
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Dental Implants in Oncology Patients versus Non-Oncology Patients: A 5-Year Retrospective Study

Abstract: Patients with a history of cancer are increasingly common in the dental office. Treating cancer patients requires a multidisciplinary team, which should include the dentist, in order to control the complications that occur in the oral cavity and also to recover the patient undergoing treatment in any of its types: surgical, medical, radiotherapeutic, or its possible combinations. Dental implants can be a safe and predictable treatment option for prosthetic rehabilitation. The aim of this paper is to describe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Overall, implant placement in oncology patients is a predictable procedure. A recent review of the literature showed a 97.16% success rate in healthy patients vs. a success rate of 93.02% in oncological patients [ 26 ]. Although, a large number of confounding parameters should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, implant placement in oncology patients is a predictable procedure. A recent review of the literature showed a 97.16% success rate in healthy patients vs. a success rate of 93.02% in oncological patients [ 26 ]. Although, a large number of confounding parameters should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The esthetic and functional sequelae of this treatment approach, particularly in advanced-stage patients, impact the ability to speak, chew, and swallow and create a negative esthetic impact on the patient’s external appearance, leading to a decline in the quality of life 4,5. The functional and esthetic rehabilitation of patients undergoing extensive resections constitutes 1 of the biggest challenges for the multidisciplinary team due to its extreme difficulty 6. The conventional removable prosthesis used over a significant defect will experience deficiencies in bone associated with inadequate soft tissue.…”
mentioning
confidence: 99%
“…4,5 The functional and esthetic rehabilitation of patients undergoing extensive resections constitutes 1 of the biggest challenges for the multidisciplinary team due to its extreme difficulty. 6 The conventional removable prosthesis used over a significant defect will experience deficiencies in bone associated with inadequate soft tissue. Moreover, the loss of occlusion vertical dimension impacts the masticatory function, phonetics, dental esthetics, and facial appearance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Providing oral and esthetic rehabilitation for patients undergoing extensive resections is crucial but represents the most significant challenge. 6,7 The surgical defect, comorbidity, patient preference, and the multidisciplinary team determine the rehabilitation method used in patients undergoing maxillectomy. 3,4 Surgical reconstruction using local flaps, (osteo)fasciocutaneous free flaps, or (osteo)myocutaneous free flaps, followed mainly by implant surgery 4 or the utilization of an obturator prosthesis, with or without implant support, 8 are among the options for rehabilitation.…”
mentioning
confidence: 99%